Microstructural and mechanical characterization of injection molded 718 superalloy powders - GÜLSOY, HAMİT ÖZKAN (ELSEVIER SCIENCE SA, 2013)
This study concerns with the determination of optimum production parameters for injection molding 718 superalloy parts. And at the same time, microstructural and mechanical characterization of these produced parts was also carried out. At the initial stage, 718 superalloy powders were mixed with a multi-component binder system for preparing feedstock. Then the prepared feedstock was granulated and shaped by injection molding. Following this operation, the shaped samples were subjected to the debinding process. These samples were sintered at different temperatures for various times. Samples sintered under the condition that gave way to the highest relative density (3 h at 1290 degrees C) were solution treated and aged respectively. Sintered, solution treated and aged samples were separately subjected to microstructural and mechanical characterization. Microstructural characterization operations such as X-ray diffraction, optical microscope (OM), scanning electron microscope (SEM), transmission electron microscope (TEM) and elemental analysis showed that using polymeric binder system led to plentiful carbide precipitates to be occurred in the injection molded samples. It is also observed that the volume fractions of the intermetallic phases (gamma' and gamma '') obtained by aging treatment were decreased due to the plentiful carbide precipitation in the samples. Mechanical characterization was performed by hardness measurements and tensile tests. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Powder injection molding; 718 Superalloy; Sintering; Microstructure; Mechanical properties; NICKEL-BASED SUPERALLOYS; BASE SUPERALLOY; HEAT-TREATMENT; INCONEL-718 ALLOY; PRECIPITATION; EVOLUTION; NIOBIUM; PHASES; DELTA